Sistema monolítico de EPS: desempenho térmico do sistema em residencia em Belém do Pará sob a análise da NBR-15575-4 - FAVACHO, Acylino Andrade (2024)
The monolithic expanded polystyrene (EPS) system is an innovative technology that meets the requirements of the Building Performance Standard (NBR15575) in relation to thermal performance. With its integrated thermal insulation, coating and finishing structure, the system offers several advantages over conventional construction techniques such as masonry enclosures. This work aims to confirm the advantages of the thermal performance of the monolithic EPS system in accordance with the guidelines of NBR15575. The advantages related to thermal performance were analyzed to evaluate the effectiveness of the system in regulating the internal temperature of buildings, in accordance with the criteria established in the standard. To this end, theoretical and practical studies were carried out, including case analysis on the use of the system in buildings. As the main result, the efficiency of the system was verified according to the requirements of the standard and the advantage of the system applied in the region of Belém do Pará. It is expected that this study will contribute to the improvement of civil construction technology in accordance with the standards and quality standards required by the market.